THE ROLE OF MOTIVATION IN SECOND LANGUAGE ACQUISITION - Rafika Nurhidayah (Jurnal Ilmiah Spectral, 2020)
This paper aims to explore the role of motivation in second language acquisition. Motivation is one of the most important factors for learning a second language proficiently. Motivation is unavoidable linked with language achievement in the sense that language achievement can not happen without motivation. In short, motivation is used as a concept for explaining the success or failure of a language learner. There are many advantages for knowing other languages but they are not absolutely necessary, and as a consequence, motivation can play an important role in learning second language. And there are many factors that can affect this motivation.